Corymorpha tropica, a new species of anthoathecate hydrozoan (Cnidaria: Hydrozoa) from Southeast Asia - Galea, Horia R. (Zootaxa, 2023)
A new species of corymorphid, Corymorpha tropica sp. nov., of common occurrence in Southeast Asia, is described. The account is based on both its hydroid and newly-released medusa. The caulus of the former is conspicuously divided into two distinct parts: a proximal, perisarc-covered, papillate, light brown to orange-colored portion, and a distal, naked, non-papillate, flesh to brick red-colored portion. The hydranth is equally variously-colored, and has either a distinctly-demarcated or a more diffuse red, circular band around its base. A whorl of long blastostyles, situated slightly above the aboral whorl of tentacles, give rise to isolated clusters of gonophores borne on short, lateral pedicels. The dispersive stage is a free-living medusa that is released without gonads from the parent hydroid. At this stage, its umbrella is bell-shaped, with a moderately developed, rounded, apical projection and scattered nematocysts on the exumbrella, and has three atentaculate, conical bulbs, as well as a main tentacle provided with a distal, large, globular nematocyst cluster and up to two intermediate knobs on its adaxial side, the position of the latter clusters being diagnostic.